REM sleep without atonia as prodromal marker of Lewy body disease: Fake news or the real deal?. (October 2019) - Rodrigues, Laís D.; Oliveira, Leandro F.; Scorza, Carla A.; Andersen, Monica L.; Tufik, Sergio; Finsterer, Josef; Scorza, Fulvio A.
Abstract: Dijkstra and collaborators provide interesting and important issue in clinical research addressing REM sleep without atonia as a possible prodromal marker for Lewy body disease, an early finding in Parkinson's disease. Though prodromal studies are relevant, it is also mandatory to consider the causes of mortality of Parkinson's disease once it is stablished, such as Sudden Unexpected Death in Parkinson's Disease.